A Review of Engineering Leadership Concept: A Way Forward - Alim Maktar; Khairun Nisa Khairuddin; Ummi Naiemah Saraih (Journal of Communication in Scientific Inquiry (JCSI), 2024)
Leadership is a critical component in business management, and in some situations, it can be vital to the survival of a company or organization. The concept of leadership has been extensively studied across various disciplines, yet the specific domain of engineering leadership remains underexplored and poorly defined. Every engineering organization, regardless of size, requires leaders and employees to execute projects to ensure their organization’s success. This review article examines the existing definitions of leadership and engineering leadership, highlighting the lack of consensus in the field. By analyzing current literature, the authors identify the key attributes and skills associated with engineering leadership and discuss their relevance to contemporary engineering practices. Our findings reveal a fragmented understanding of engineering leadership, underscoring the need for further empirical studies to develop a cohesive and comprehensive definition. This article aims to provide a foundational understanding of engineering leadership and proposes directions for future research to bridge the gaps in the current knowledge, thereby paving the way for the development of robust theoretical and practical frameworks in engineering leadership. This paper focuses on leadership in the engineering context as the engineering sector plays a vital role in addressing sustainable development on a local, national, regional and global level. The concept of engineering leadership is dynamic across countries and sectors, thus merits more attention from scholars to explore the dynamism of the concept.